Nilai Waktu dalam Ungkapan Tradisional Bugis di Lombok: Sebuah Kajian Bahasa dan Budaya - NFN Syarifuddin (MABASAN, 2009)
Bugies is one of ethnic that have lived nomad. They can be finding at any coastal area in Indonesia, and one of them is in Lombok Island. To holding out and succeed live in the foreign, the bugisnes must be apreciate times. The times reflection of traditional expression such as fore fathers advice and papaseng. The papaseng indicates that the times are always changes. A change of times can be happens such as change of an actor, activities, or something in real life. Then, one of positive thing that always do in Bugiesness real life is appriciate the times.The values which are consists in it always be guide for whole Bugisnes to realizing wishes in their real life.